Epigenetically modulated miR-1224 suppresses the proliferation of HCC through CREB-mediated activation of YAP signaling pathway - Shikun Yang; Wei Jiang; Wenjie Yang; Chao Yang; Xinchen Yang; Keyan Chen; Yuanchang Hu; Gefenqiang Shen; Ling Lu; Feng Cheng; Feng Zhang; Jianhua Rao; et al. (Elsevier, 2021)
Mounting evidence has demonstrated that microRNA-1224 (miR-1224) is commonly downregulated and serves as a tumor suppressor in multiple malignancies. However, the role and mechanisms responsible for miR-1224 in hepatocellular carcinoma (HCC) remain unclear. In this study, we found that the expression of miR-1224 was downregulated in HCC. Low miR-1224 expression was associated with poor clinicopathologic features and short overall survival. Moreover, the methylation status of putative CpG islands was also found to be an important part in the modulation of miR-1224 expression. miR-1224 could induce HCC cells to arrest in G0/G1 phase and inhibited the proliferation of HCC cells both in vitro and in vivo. Mechanistic investigation showed that by binding with cyclic AMP (cAMP)-response element binding protein (CREB) miR-1224 could repress the transcription and the activation of Yes-associated protein (YAP) signaling pathway. Furthermore, the expression of miR-1224 was inhibited by CREB through EZH2-mediated histone 3 lysine 27 (H3K27me3) on miR-1224 promoter, thus forming a positive feedback circuit. Our findings identify a miR-1224/CREB feedback loop for HCC progression and that blocking this circuit may represent a promising target for HCC treatment.